Tecnobiografia: um olhar sobre a agência do professor em produções multimodais na perspectiva dos multiletramentos - Santos, Gabriela Krause dos (Universidade do Vale do Rio dos Sinos, 2022)
The technological era which we live has increasingly changed the way we relate to each other, how we live in society and how we communicate with others. On the other hand, in education, there is resistance, unpreparedness, as well as a lack of investment in teacher training (initial and continuing), so that teachers can appropriate themselves of digital technologies and learn to work WITH them. With this in mind, we ask ourselves: How can technobiographies (as a Digital Storytelling) serve as potentiators of the teacher's agency in training while developing their multiliteracies? To answer this question, we established a general objective, a) to understand how working with technobiography provides the development of multiliteracies. We also define the following specific objectives. 1) identify how teachers in training build themselves as agents of change in their own practices; 2) analyze the ways in which students/teachers construct their meanings in multimodal productions. This research is qualitative-interpretative, of an ethnographic nature, and the data analyzed here were generated in an undergraduate Letras course (Teaching Language and Literature), on literacy studies, at a community university in the south of Brazil. We analyzed three technobiographies produced by the students/teachers according to the Transpositional Grammar (COPE; KALANTZIS, 2021) and Pedagogy of Design (KALANTZIS, COPE E PINHEIRO, 2020), and the journals written after the production. Based on the analyses, it is possible to see that the process of construction of meaning is complex, and the experience of working WITH the technologies provides the development of the teacher's agency, and other literacies necessary for the 21st century.
Keywords: Tecnobiografia; Agência; Narrativas digitais; Multiletramentos; Formação de professores; Technobiography; Agency; Digital storytelling; Multiliteracy; Teacher training; ACCNPQ::Lingüística, Letras e Artes::Lingüística